Those missing yams again! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Ok, it s over. Mr A A Olaniyan from nothing less than the National Horticultural Research Institute in Ibadan, Nigeria, joins the masses of readers who still remind us of our error of publishing a photo a woman with a basket of cassava with a...